Scrapbooking for home décor : how to create frames, boxes, and other beautiful items from photographs and family memories - Windham, Candice (Design Originals, an imprint of Fox Chapel Publishing, 2012)
"Scrapbooking is a wonderful past-time that has been used by countless families across America to preserve family history and memories. But what comes after you've created your scrapbook collection? Which book is put out on the coffee table, and which is stored away? With this book, you will never have to pick and choose between your favorite memories again. Award-winning author Candice Windham will show you how to turn your scrapbooking photos into beautiful pieces of home decor that can be proudly displayed throughout your home. Inside you'll find 13 fabulous projects that will take your scrapbooking experience to a whole new level. Learn how to create a stationery box featuring pictures of your family or how to put together a recipe box covered with some of mom's favorite sayings. Windham offers tips and tricks for working with materials like papers, adhesives, and paint techniques for stamping, shading, inking, and creating custom embellishments. Whether you're new to scrapbooking or have been doing it for years, this book will provide you with a unique project that is creative, fun, and functional"--